The effectiveness of eradication therapy of the 1st line of Helicobacter pylori infection in patients with type 2 diabetes mellitus - Igor V. Maev; Ashot M. Mkrtumyan; Luiza G. Bektemirova; Dmitry N. Andreev; Diana T. Dicheva (Терапевтический архив, 2022)
Aim. Evaluation of the efficacy and safety of eradication therapy of infection Helicobacter pylori in patients with H. pylori- associated pathology of the upper gastrointestinal tract and concomitant type 2 diabetes mellitus (DM).